Impressed Ware blade production of Northern Dalmatia (Eastern Adriatic, Croatia) in the context of Neolithisation - Sonja Kačar (Documenta Praehistorica, 2019)
The lithic assemblages from the principal early Neolithic sites in Northern Dalmatia have been analysed with respect to the technological aspects and principles of schéma and chaîne opératoire, débitage economy and raw material economy. Northern Dalmatia, the most fertile region of the Eastern Adriatic, hosts the most important Neolithic open-air sites. Early Neolithic is associated with the Impressed Ware culture and dates back to c. 6000–5400 cal BC. The Early Neolithic lithic assemblages are characterized by the pressure blade production techniques on high-quality Gargano cherts reflecting important socio-economic and technical mutations that are specific to the Neolithic. Moreover, the almost exclusive reliance on these exogenous cherts emphasizes the social aspects of such networks and reinforces the idea of cultural uniformity of Dalmatian and Apulian Impressed Ware.